Discovery of a small protein-encoding cis-regulatory overlapping gene of the tumor suppressor gene Scribble in humans - Yuhta Nomura (Nature Portfolio, 2021)
Yuhta Nomura and Naoshi Dohmae report the discovery of a small protein-coding gene that overlaps the tumor suppressor gene Scribble. Their data suggest that the overlapping gene, oSCRIB, limits the translation of downstream Scribble and may have important implications in cancer.